2012
DOI: 10.1371/journal.pone.0037794
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphic Regulation of Body Weight Dynamics and Adipose Tissue Lipolysis

Abstract: BackgroundSuccessful reduction of body weight (BW) is often followed by recidivism to obesity. BW-changes including BW-loss and -regain is associated with marked alterations in energy expenditure (EE) and adipose tissue (AT) metabolism. Since these processes are sex-specifically controlled, we investigated sexual dimorphisms in metabolic processes during BW-dynamics (gain-loss-regain).Research DesignObesity was induced in C57BL/6J male (m) and female (f) mice by 15 weeks high-fat diet (HFD) feeding. Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 35 publications
7
44
1
Order By: Relevance
“…Unlike previous studies ( 41, 71 ), we were not able to detect any increase in either serum FFA or glycerol levels in our male wild-type mice after T0901317 injections compared with saline controls. This difference may be due to the use of different genders in these experiments and the length of fasting prior to blood collection ( 41,42,71,72 ). Finally, studies in primary mouse adipocytes confi rmed our fi ndings in the animal models.…”
Section: Discussionmentioning
confidence: 56%
“…Unlike previous studies ( 41, 71 ), we were not able to detect any increase in either serum FFA or glycerol levels in our male wild-type mice after T0901317 injections compared with saline controls. This difference may be due to the use of different genders in these experiments and the length of fasting prior to blood collection ( 41,42,71,72 ). Finally, studies in primary mouse adipocytes confi rmed our fi ndings in the animal models.…”
Section: Discussionmentioning
confidence: 56%
“…RER is a sensitive measure of metabolic rate and has been reported to be altered as the result of a number of loss of function mutations in the mouse (73)(74)(75). An increased basal metabolic rate and RER were observed in fat-specific insulin receptor knock-out mice (76).…”
Section: Conditional O-glcnacase Knockout Impacts Metabolismmentioning
confidence: 99%
“…Indeed, crucial roles of female sex hormones in adipose tissue metabolism have been demonstrated [16, 17], and it has been shown that estrogen can directly activate lipolysis through estrogen receptor alpha signaling in adipocytes [1719]. In addition to direct activation of lipolysis, sex hormones influence body fat distribution, and subcutaneous fat is more abundant in women [2].…”
Section: Introductionmentioning
confidence: 99%